2010 IEEE International Conference on Robotics and Automation 2010
DOI: 10.1109/robot.2010.5509525
|View full text |Cite
|
Sign up to set email alerts
|

Graph theory roots of spatial operators for kinematics and dynamics

Abstract: 19The passive sizing system consists of a series of low-profile pulleys attached to the front and back of the shoulder bearings on a spacesuit soft upper torso (SUT), textile cord or stainless steel cable, and a modified commercial ratchet mechanism. The cord/cable is routed through the pulleys and attached to the ratchet mechanism mounted on the front of the spacesuit within reach of the suited subject. Upon actuating the ratchet mechanism, the shoulder bearing breadth is changed, providing variable upper tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Song and Amato [27] apply the analysis of tree-like articulated systems to folding. Jain [28] uses tree graphs for the dynamic analysis of multi-body systems; tree-systems also appear describing dynamic systems in Garcia de Jalon [29]. Tree articulated systems and their graph representation are also studied in [30] for the analysis and control of mechanical systems, where they are named forking linkages.…”
Section: Introductionmentioning
confidence: 99%
“…Song and Amato [27] apply the analysis of tree-like articulated systems to folding. Jain [28] uses tree graphs for the dynamic analysis of multi-body systems; tree-systems also appear describing dynamic systems in Garcia de Jalon [29]. Tree articulated systems and their graph representation are also studied in [30] for the analysis and control of mechanical systems, where they are named forking linkages.…”
Section: Introductionmentioning
confidence: 99%
“…Kinematic analysis of tree topologies for applications in modular robots and robotic hands can be found in [1], [2], and [3], and dynamic analysis is found in [4] and [5]. Structural synthesis for multiple fingers with no wrist is also considered in [2], and in [6] for grasping and manipulation requirements.…”
Section: S a Vector ŝ A Quaternion Or Dual Quaternion ŵ A Dual Number...mentioning
confidence: 99%
“…Kinematic and dynamic analysis of tree topologies is studied in de Jalon and , Jain (2010) and Tischler et al (1995), and type synthesis of tree topologies can be found in Lee and Tsai (2002) for grasping and manipulation requirements. The dimensional synthesis of the tree topologies has been explored in Simo-Serra et al (2011), Simo-Serra et al (2012 and more extensively in Simo-Serra and Perez-Gracia (2014).…”
Section: Introductionmentioning
confidence: 99%